Strategies to enhance application of SIRIM eco-label products in construction industry - Ahamad, Abdul Hadi (2015)
Environmentally product appears growing steadily around the developed world and also some developing countries. The Malaysian government also has responded very positively to this matter. In 1996, Standards and Industrial Research Institute of Malaysia (SIRIM) launched the national eco-labelling program verifying products according to environmental criteria as tools and initiatives to express concern and support to sustainable development. Taking into consideration the infancy stage of the Malaysia green marketing initiative, this study therefore conducted with the aim to suggest possible strategies to increase the application level of eco-label product in Malaysian construction industry. Survey were conducted via questionnaire and interview method with respondents from various construction companies among construction players that have involved and experienced with green project. Data obtained were analysed using Average Index method. The result shown that, the application and awareness level among construction players were relatively acceptable which still can be enhanced with most of the significant strategies proposed.